Cardenal, one and many: polyphony in his work - Pastor Alonso, Mª Ángeles (Anales de Literatura Hispanoamericana, 2021)
This paper intends to discern the multiple voices present in Ernesto Cardenal’s poetry. Outer objective voices with different intentions are present in his work together with a personal voice which increasingly tends to autobiographical experience. In addition, the transmission of other authors’ messages is frequent too. This way, his work is opened to intertextuality, multiplying thus the chances for different readings and involving the reader in the building of the poem. In this paper we aim to systematize the different voices and to trace them throught his extensive poetic production, focusing on his most representative book, Cántico cósmico.